Functional studies of p.R132C, p.R149C, p.M283V, p.E431K, and a novel c.652-2A>G mutations of the CYP21A2 gene - Taboas, Melisa Ivana (2014)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is the most frequent inborn error of metabolism and accounts for 90–95% of CAH cases. In the present work, we analyzed the functional consequence of four novel previously reported point CYP21A2 mutations -p.R132C, p.R149C, p.M283V, p.E431K- found in Argentinean 21-hydroxylase deficient patients. In addition, we report an acceptor splice site novel point mutation, c.652-2A.G, found in a classical patient in compound heterozygosity with the rare p.R483Q mutation. We performed bioinformatic and functional assays to evaluate the biological implication of the novel mutation. Our analyses revealed that the residual enzymatic activity of the isolated mutants coding for CYP21A2 aminoacidic substitutions was reduced to a lesser than 50% of the wild type with both progesterone and 17-OH progesterone as substrates. Accordingly, all the variants would predict mild non-classical alleles. In one non-classical patient, the p.E431K mutation was found in cis with the p.D322G one. The highest decrease in enzyme activity was obtained when both mutations were assayed in the same construction, with a residual activity most likely related to the simple virilizing form of the disease. For the c.652-2A.G mutation, bioinformatic tools predicted the putative use of two different cryptic splicing sites. Nevertheless, functional analyses revealed the use of only one cryptic splice acceptor site located within exon 6, leading to the appearance of an mRNA with a 16 nt deletion. A severe allele is strongly suggested due to the presence of a premature stop codon in the protein only 12 nt downstream.